Association between indel polymorphism (rs145204276) in the promoter region of lncRNA GAS5 and the risk of febrile convulsion. Issue 9 (17th January 2019) - Xiang, Wenna; Li, Zhishu; Lin, Zongze; You, Keyou; Pan, Minli; Zheng, Ge
Abstract: Background: This study aimed to explore the regulatory relationship between growth arrest special 5 (GAS5) and interleukin‐1β (IL‐1β) implicated in the development of febrile seizure (FS). Method: The presence of FS and the genotype of GAS5 were used as two different indicators to divide the 50 newborn babies, recruited in this study, into different groups. The potential regulatory relationship among GAS5, miR‐21, and IL‐1β was identified by measuring their expression using quantitative reverse‐transcription polymerase chain reaction and immunohistochemistry assays among different sample groups. Computational analyses and luciferase assays were also conducted to verify the interaction between GAS5, miR‐21, and IL‐1β. Result: GAS5 and IL‐1β expression was upregulated in cells collected from FS patients or genotyped as INS/DEL and DEL/DEL, whereas the expression of miR‐21 was decreased in above samples, indicating a negative relationship between miR‐21 and GAS5/IL‐1β. Results of the computational analysis showed that miR‐21 directly bound to and increased the expression of GAS5, whereas the expression of IL‐1β was suppressed by miR‐21. In the presence of GAS5, the expression of miR‐21 was lowered, whereas the expression of IL‐1β was increased. Conclusion: The results obtained in this study supported the conclusion that GAS5 negatively regulated the expression of miR‐21, which in turn negatively regulated the expression IL‐1β. Therefore, the overexpression of GAS5 could decrease the magnitude of FS. Abstract : This study aimed to explore the regulatory relationship between growth arrest special 5 (GAS5) and interleukin‐1β (IL‐1β) implicated in the development of febrile seizure (FS). The results obtained in this study supported the conclusion that GAS5 negatively regulated the expression of miR‐21, which in turn negatively regulated the expression IL‐1β. Therefore, the overexpression of GAS5 could decrease the magnitude of FS.